Consumers' Perception towards Miraculous Claims of Brands with Aesthetic Appeal - Saurabh; Mahajan, Akhil (Indian Journal of Marketing, 2013)
Often, consumers are targeted with large claims of various brands that boast of miraculous results for products with an aesthetic appeal. This paper uses the exploratory design with mixed methodology to explore the ranks of miraculous claims out of the inventory of products and then uses the factor loading method to gauge the perception of the consumers. The key factors were identified after conducting a review of literature, and then the factor loadings were applied to derive the ranking and obtain the variance of the factors of perception. The results of this study provide a framework to work upon the marketing aspect of miraculous claims made by brands that may be in congruence to the aesthetic appeal for the brand managers and researchers. The study shows that Technical Product Specifications and Evidence were the most effective in enhancing consumers' beliefs, and this factor leads to a positive perception in the minds of the consumers about products with an aesthetic appeal. Statement of Contribution: The paper empirically gauges the factors influencing respondents' perception of the products with miraculous claims with an aesthetic appeal. This study would help product managers and researchers in designing marketing communication strategies that would lead to the creation of a positive perception about the brands in the minds of the consumers, which might positively influence their purchase decision of such products.